FITOREMEDIASI PADA MEDIA TANAH YANG MENGANDUNG Cu DENGAN TANAMAN KANGKUNG DARAT - Haruna, Elvira T; Isa, Ishak; Suleman, Nita (Sainstek, 2012)
One of the restoration of contaminated environmental quality method is using phytoremediation techniques. That is recovery contaminated environment using plants. This research studied the ability of kangkung darat (Ipome reptans) to absorb metallic copper and to find out which part of the Kangkung Darat that absorb most of the metal Cu, also to know the difference between absorption and kangkung darat are harvested at 2, 4 and 6 weeks. The research activities are carried out by planting kangkung darat in a contaminated soil media and in the flush of copper metal with a solution of Cu mg / L two times a day. Samples of kangkung darat have been taken from accordance with plant age (2, 4 and 6 weeks), and plant parts (roots, stems and leaves). Used in Atomic Absorption Spectroscopy (AAS) Simatzu type AA to measure the content of Cu in the sample. Results obtained from this study that Cu accumulation in plants is mainly found in the roots. On the kangkung darat were 2 weeks of Cu contained as much as 5.3403 ppm in the roots, stems and leaves of 2.6637 5.1117. At the age of 4 weeks in a row at the root, stem leaves are 10.6998, 5.8281 and 2.0666 ppm. Mean, at the age of 6 weeks at the root of 10.4605, the leaves on the stem 7.7839 and 9.1863 ppm. From the research results can be concluded that kangkung darat could be used as fitoremediator Cu metal contaminated soil.